Activation of 5-HT2C (but not 5-HT1A) receptors in the amygdala enhances fear-induced antinociception: Blockade with local 5-HT2C antagonist or systemic fluoxetine - Tavares, Lígia Renata Rodrigues [UNESP]; Baptista-de-Souza, Daniela; Canto-de-Souza, Azair [UNESP] (Elsevier, 2018)
It is well-known that the exposure of rodents to threatening environments [e.g., the open arm of the elevated-plus maze (EPM)] elicits pain inhibition. Systemic and/or intracerebral [e.g., periaqueductal gray matter, amygdala) injections of antiaversive drugs [e.g., serotonin (5-HT) ligands, selective serotonin reuptake inhibitors (SSRIs)] have been used to change EPM-open arm confinement induced antinociception (OAA). Here, we investigated (i) the role of the 5-HT1A and 5-HT2C receptors located in the amygdaloid complex on OAA as well as (ii) the effects of systemic pretreatment with fluoxetine (an SSRI) on the effects of intra-amygdala injections of 8-OH-DPAT (a 5-HT1A agonist) or MK-212 (a 5-HT2C agonist) on nociception in mice confined to the open arm or enclosed arm of the EPM. Nociception was assessed by the writhing test. Intra-amygdala injections of 8-OH-DPAT (10 nmol) or MK-212 (0.63 nmol) produced a pronociceptive effect and intensified OAA, respectively. Fluoxetine (2.5 mg/kg, intraperitoneally) did not change 8-OH-DPAT effects on nociception but antagonized the enhancement of the OAA produced by MK-212. Interestingly, prior injection of SB 242084 (a selective 5-HT2C antagonist) into the amygdala also blocked the MK-212 effects on OAA. These results indicate that 5-HT may facilitate nociception and intensify OAA, respectively, at 5-HT1A and 5-HT2C receptors located in the amygdala of mice. The impairment produced by systemic fluoxetine on the OAA enhancement provoked by intra-amygdala MK-212 suggests that this type of fear-induced antinociception may be modulated by SSRIs.
Keywords: 5-HT1A and 5-HT2C receptors; Amygdala; Antinociception; Elevated plus maze; Fluoxetine; Mice